No data, no deal? Impact measurement and capital flows to achieve climate-compatible growth - Carew-Jones, G; Money, A (Climate Compatible Growth, 2024)
Impact measurement and management (IMM) is increasingly being adopted as a method to bring integrity and transparency to the impact investment industry, motivated by claims that ‘impact-washing’ is common amongst organisations adopting this emerging investment strategy. With limited literature to date addressing this phenomenon, this working paper asks how impact measurement is defining investor decision making, and what the implications of this are for the supply of impact capital, especially in emerging markets. Qualitative semi-structured interviews were undertaken with impact investors and impact intermediary organisations, revealing that approaches to impact measurement are driven by underlying investor motivations between different organisation types. A general trend towards increasing impact measurement is clear, characterised by little cross-industry consistency and a slow movement towards increasing standardisation and sophistication of approaches. The core finding of this study is that the shift towards increasing IMM risks entrenching existing inequalities in access to capital. Investees in emerging markets need support in measuring and managing impact, with a dialogue between investors and investees being required to ensure that the goals and methods of IMM are co-defined towards optimal outcomes. Options to address these challenges through public policy are offered; and the case of Zambia’s Constituency Development Fund is explored as a prototypical example of how impact measurement could unlock investment towards a large group of climate-compatible growth projects and ventures.